Best in CLASS (conceptual learning application for sustainable schools) - Carter, David; Green, Ryan (Kansas State University, 2011)
“Best in CLASS (Conceptual Learning Application for Sustainable Schools)” is a combination training module/computer game designed to raise sustainability awareness for high school seniors and provide high school teachers with an interactive tool to enhance education efforts. The objectives of this training is to promote energy efficiency and sustainability education and realistic practices in schools, encourage high school seniors to pursue education and careers in engineering and energy management, and facilitate active learning and engagement on energy efficiency through on-line environmental educational resources and tools. Video training modules would be developed in 5-7 energy efficiency/sustainability principles. Students would then enter the “virtual school” where they can make changes to increase the school’s sustainability efforts. Students from K-State’s Computing and Information Sciences Department within the College of Engineering will present prototypes they are developing for this project.
Keywords: Training modules; Computer games; HIgh school students; Sustainability awareness